Long‐term efficacy of no‐touch radiofrequency ablation in the treatment of single small hepatocellular carcinoma: A single center long‐term follow‐up study - Guodong Wu; Jing Li; Changfeng Li; Xia Ou; Kai Feng; Feng Xia; Zhiyu Chen; Leida Zhang; Kuansheng Ma (Cancer Medicine, 2023)
Abstract Objective To evaluate the long‐term efficacy of no‐touch radiofrequency ablation (NT‐RFA) for treating single hepatocellular carcinoma (HCC) less than 3 cm. Methods A total of 331 patients with HCC less than 3 cm undergoing RFA in Southwest Hospital from 2015 to 2020 were analyzed retrospectively. All patients were divided into NT‐RFA group (n = 113) and conventional RFA (C‐RFA) group (n = 218). The survival rate, local tumor progression (LTP) and intrahepatic distant recurrence (IDR) of the two groups were calculated and compared. Results A significant difference was observed in ablation range (p = 0.000) and safety margin (p = 0.000) between the two groups. The 1‐, 2‐, 3‐, 4‐and 5‐year overall survival (OS) rates in NT‐RFA and C‐RFA group were 99.12%, 93.73%, 76.18%, 57.00%, 45.17% and 99.08%, 89.91%, 71.26%, 54.28%, 41.77%, respectively. There was no significant difference between the two groups (p = 0.281). The 1‐, 2‐, 3‐, 4‐and 5‐year recurrence‐free survival (RFS) rates in NT‐RFA and C‐RFA group were 78.51%, 52.59%, 41.02%, 34.36%, 30.92% and 68.81%, 44.95%, 30.88%, 23.73%, 22.88%, respectively. The two groups differed significantly (p = 0.044). The 1‐, 3‐and 5‐year LTP‐free survival rates in NT‐RFA and C‐RFA group were 87.12%, 74.99%, 72.32% and 75.75%, 65.52%, 65.52%, respectively. The two groups also differed significantly (p = 0.024). Furthermore, the RFS rates of D ≤ 2 cm subgroups in NT‐RFA and C‐RFA groups differed significantly (p = 0.037), while the RFS rates of 2 cm < D ≤ 3 cm subgroups in two groups showed no significant difference (p = 0.578). Conclusions The RFS rates of single HCC less than 3 cm treated by NT‐RFA was significantly higher than that of C‐RFA. Due to a larger ablation range and safety margin, NT‐RFA could significantly reduce LTP and improve RFS. Dual‐electrode NT‐RFA can significantly improve the RFS rate of patients with HCC less than 2 cm, but there is no obvious advantage compared with C‐RFA in the treatment of HCC over 2 cm.